2019
DOI: 10.1038/s41388-018-0633-1
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase IIβ-binding protein 1 activates expression of E2F1 and p73 in HPV-positive cells for genome amplification upon epithelial differentiation

Abstract: High-risk human papillomaviruses (HPVs) constitutively activate the ataxia telangiectasia mutated (ATM) and the ataxia telangiectasia and Rad3-related (ATR) DNA damage repair pathways for viral genome amplification. HPVs activate these pathways through the immune regulator STAT-5. For the ATR pathway, STAT-5 increases expression of the topoisomerase IIβ-binding protein 1 (TopBP1), a scaffold protein that binds ATR and recruits it to sites of DNA damage. TopBP1 also acts as a transcriptional regulator and we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…HPV-positive cells with either ATR or TopBP1 knockdown (24) remain proliferative and do not become growth arrested. We screened downstream targets of TopBP1 by RNA-seq approaches and found a number of potential downstream targets related to immune response (24), which are also detected in ATR knockdown cells (Fig. 6a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV-positive cells with either ATR or TopBP1 knockdown (24) remain proliferative and do not become growth arrested. We screened downstream targets of TopBP1 by RNA-seq approaches and found a number of potential downstream targets related to immune response (24), which are also detected in ATR knockdown cells (Fig. 6a).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, functional enrichment analysis was performed with Qiagen's Ingenuity Pathway Analysis (IPA). The work of TopBP1 knockdown RNA-seq has been published in our previous work (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription regulation plays key roles in HPV productive life cycle. For example, the transcription factor family of p63 and p73 is critical for HPV genome amplification [ 53 , 54 ]. Other transcription factors that regulate HPV viral transcription were summarized in the previous review [ 55 ].…”
Section: Hpv Life Cyclementioning
confidence: 99%
“…TopBP1 is a scaffold protein containing 9 BRCT (BRCA1 carboxyl terminus) domains and is involved in many aspects of nucleic acid metabolism, including DNA replication and repair [ 61 ]. Studies from several groups, including ours, have indicated that TopBP1 is important in HPV replication [ 43 , 44 , 45 , 48 , 62 , 63 ]. TopBP1 is an essential protein; therefore we sought to identify host enzymes that regulate TopBP1 as potential modulators of E1–E2 replication.…”
Section: Using the Hpv16 Replication Assay To Study Lesions In Hosmentioning
confidence: 99%